The evaluation of various morphological aspects of septal cartilage-a cadaveric study: a 6 months observation study in KLEs, Dr. Prabhakar kore hospital, Belagavi - Chandra, Indresh; Bellad, Shama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The nasal septum provides support for the portion of cartilaginous nasal dorsum, and it is responsible for determining the projection of the nasal tip. Septal cartilage plays an important role as a donor graft material in modern rhinoplasty. An anatomical study was performed on 10 adult cadavers. The excised septal cartilage was placed on grid paper; digital images were taken; all septal cartilage was divided into nine equivalent quadrants; and quantitative measurements for length, height, and area were calculated and compared. The average length of the septum was 35.8 mm, while the average height was 25.9 mm. The average septal area was 679.7 mm2. The septal thickness mean values were analysed in nine quadrants, ranging from 1.21 to 2.08 mm. Specifically, the central and cranial areas were thickest, and the area corresponding to the L-strut was thinnest. Anatomical variations of the thickness of septal cartilage excisions were found to be statistically significant, and these differences play an important role in the proper selection of the septal grafts.